1987
DOI: 10.1073/pnas.84.11.3623
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of phospholipase A2 activity in bovine rod outer segments by the beta gamma subunits of transducin and its inhibition by the alpha subunit.

Abstract: In the rod outer segments (ROS) of bovine retina, light activation of phospholipase A2 has been shown to occur by a transducin-dependent mechanism. In this report, the transducin-mediated stimulation of phospholipase A2 is shown to require dissociation of the apr heterotrimer. Addition of transducin to dark-adapted transducin-poor ROS stimulated phospholipase A2 activity only with coincident exposure to white light or, in the dark, with addition of the hydrolysis-resistant GTP analog, guanosine 5'-[y-thio]trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(116 citation statements)
references
References 39 publications
(24 reference statements)
1
114
0
1
Order By: Relevance
“…Another question concerns the effects of major input signals like norepinephrine or light on PG production in chick pineal cells. Indeed, previous studies on retinal photoreceptors have indicated that light stimulates phospholipase A, activity (Jelsema, 1987;Jelsema and Axelrod, 1987), which might lead to an increase in PG synthesis. Although these data do not fit with the inhibitory effect oflight on NAT activity, the possible role of PGs in pineal phototransduction should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Another question concerns the effects of major input signals like norepinephrine or light on PG production in chick pineal cells. Indeed, previous studies on retinal photoreceptors have indicated that light stimulates phospholipase A, activity (Jelsema, 1987;Jelsema and Axelrod, 1987), which might lead to an increase in PG synthesis. Although these data do not fit with the inhibitory effect oflight on NAT activity, the possible role of PGs in pineal phototransduction should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…From these data, Vellani et al (2000) proposed that polyunsaturated fats interfere with calcium entry into the channel by binding near its extracellular face. Light activates phospholipase A2 (Jelsema and Axelrod, 1987) leading to a light-induced increase of arachidonic acid and docosohexanoic acid release (Jung and Reme, 1994;Reinboth et al, 1996). Retinoid levels also are increased by light (McCaffery et al, 1996).…”
Section: 27mentioning
confidence: 99%
“…subunits may also be involved in controlling effector activity. Thus, lit dimers have been reported to stimulate phospholipase A2 [6], open atrial mu~carinic K* channels [7], inhibit type I adenylyl Correspot~d~'nce address: P. Gierschik, Molecular Pharmacolog), Division, German Cancer Research Center, lm Neuenheimer Feld 280/III, 6900 Heidelberg, Germany. Fax: (49) (6221) 423 352.…”
Section: Introductionmentioning
confidence: 99%